Assessing the Competitive Performance of National and International Higher Education Institutions; Advances in Social Science, Education and Humanities Research; Vol. 53 : International Conference on Social Science and Higher Education (ICSSHE 2016) - Spitsin V. V. Vladislav Vladimirovich; Vorobjeva E. S. Ekaterina Sergeevna; Krakovetskaya I. V. Inna Valentinovna; Osokin G. E. Georgy Evgenievich (2016, 2016)
Title screen